Induction of Autophagy by Sera From Women With Ovarian Hyperstimulation Syndrome: Potential Predictive Marker [2OP]. (May 2018) - Minis, Evelyn; Irani, Mohamad; Nasioudis, Dimitrios; Witkin, Steven S.; Spandorfer, Steven D.
Abstract : INTRODUCTION: Ovarian Hyperstimulation Syndrome (OHSS) affects 3–10% of women undergoing IVF. Identifying predictive biomarkers of OHSS can help its prevention. Given that autophagy is implicated in the regulation of ovulation, we examined the differential induction of autophagy by sera from women with OHSS and controls. METHODS: Sera were obtained before stimulation from 75 women at risk for OHSS (AMH>2 ng/mL); 34 of whom subsequently developed OHSS. The remaining 41 women served as controls. Sera were incubated for 48 hours with peripheral blood mononuclear cells (PBMCs) from a healthy donor, the PBMCs lysed and the level of autophagy determined by measuring the p62 (sequestrome-1) level. Cytoplasmic p62 is consumed during autophagy and so the p62 concentration is inversely related to the extent of autophagy. The p62 values between groups were compared by the Mann-Whitney test. RESULTS: There were no differences in age (34±5.3 vs 33.05±3.8 years), body mass index (23.4±3.5 vs 23.84.6 kg/m 2 ), parity (0.2±0.5 vs 0.2±0.5) or number of harvested oocytes (25.6±5 vs 25.9±10.67) ( P >.05) between the two groups. Median PBMC p62 levels were lower (autophagy was higher) following incubation with sera from women who developed OHSS (5.85 ng/mL) than with sera from controls (7.31 ng/mL) ( P =.03). CONCLUSION: Baseline sera from women who developed OHSS induced a higher level of autophagy in PBMCs than did at risk women who did not develop OHSS. Excessive autophagy induction in the ovary may increase susceptibility to OHSS. The extent of autophagy induction by sera obtained prior to undergoing IVF could be a predictive marker of OHSS.